1971
DOI: 10.1111/j.1469-8137.1971.tb02540.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Root System of Barley

Abstract: Summary The lengths of branched and unbranched axis, the density of branching, and the change in length of laterals along the axis (called the root profile) were determined on roots of Maris Badger and Proctor barley (Hordemn vulgare L.) grown in water culture under complete nutrient supply and deficiencies of potassium and phosphorus. The most striking observations were (a) 50–75% reductions in the length of unbranched axis caused by nutrient deficiency, (b) marked curvilinearity in the profile under all nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Evidence of this has been found not only in intact plants but also in defoliated plants (Evans 1971) and ones mutilated by removal of the tips of the root axes (Hackett 1971).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Evidence of this has been found not only in intact plants but also in defoliated plants (Evans 1971) and ones mutilated by removal of the tips of the root axes (Hackett 1971).…”
Section: Introductionmentioning
confidence: 99%
“…The morphological terms used in this paper are applied in accordance with the definitions given by Hackett (1968Hackett ( , 1971, with the exception that, following Barley (1970), the classes of laterals are now termed first-order, second-order, and thirdorder instead of primary, secondary. and tertiary.…”
Section: The Model (A) Terminologymentioning
confidence: 99%
See 2 more Smart Citations
“…Because published data imply that ba and qf vary within quite narrow limits (Weaver, Kramer, and Reed 1924;May, Chapman, and Aspinall 1965;Hackett and Bartlett 1971), and because b f and qs were found from manipulation of the model to have small effects on 1 when vf was at or below the standard value, it can be suggested that the constancy of 1 in intact roots is due primarily to the existence of ceilings to va, vI> and Vs, and secondarily to the characteristic expression of tf, t s, ba, and qf' Within these constraints, wide variation in root form is obviously possible, and most of it would be expected to give roughly constant values of 1. Thus it can be perceived why the phenomenon has been observed in experiments where the relevant data have been collected, and it can be expected that it will be commonly observed in the future.…”
Section: (C) Conclusionmentioning
confidence: 99%